On some recent Fitchian arguments. - Small, Julian D (Analysis, 2024)
Both Jago, in his 2020 article 'A short argument for truthmaker maximalism' and his 2021 article 'Which Fitch?', and Loss in his 2021 article 'There are no fundamental facts', employ arguments similar to that familiar from the Church–Fitch Paradox to infer some substantial metaphysical claims from their mere logical possibility. Trueman in his 2022 article 'Truthmaking, grounding and Fitch's paradox' and Nyseth in his 2022 article 'Fitch's paradox and truthmaking' respond by using exactly the same kind of argument to prove contrary theses. Intended as bad company objections, these counterarguments cast doubt on the original arguments, but do not actually identify their flaw. This paper aims to fill this gap.